Banking in Developing Countries in the 1990s - Hanson, James A. (World Bank, Washington, DC, 2014)
During the 1990s commercial bank deposits and capital rose relative to GDP in the major developing countries. This rise largely reflected the dramatic fall in inflation of the 1990s and financial liberalization. But much of this growth in banks' loanable funds was absorbed by increased net holdings of central bank debt and of government debt. Much of the rise in government debt reflected post-crisis restructurings, notably in Brazil, Indonesia, and Mexico, but rising deficits also played a role. Bank intermediation between depositors and private sector borrowers remained limited in many countries despite financial liberalization. The post-crisis restructurings raise two important issues: the poor performance of loans that was revealed by the crises and the future crowding-out that will result from the spreading-out of the cost of the crisis over time and the inability to retire the restructuring-related debt. The absorption of deposits in nonprivate sector credit, the growth of offshore finance of the private sector, and the poor performance of loans suggest a weakening of the link between the traditional measure of financial depth, M2/GDP, and economic growth and development. The changes in the 1990s also raise issues such as the potential for future deposit growth, the riskiness of bank portfolios, banks' increased dependence on government solvency, the access to credit for firms unable to access global markets, the foreign exchange exposure of countries, and the implications of the ongoing changes in regulation and supervision.